The development of silicon nanowire as sensing material and its applications - Abdul Rashid, Jahwarhar Izuan; Abdullah, Jaafar; Yusof, Nor Azah; Hajian, Reza (Hindawi Publishing Corporation, 2013)
The application of silicon nanowire (SiNW) as a sensing nanomaterial for detection of biological and chemical species has gained attention due to its unique properties. In this review, a short description is also demonstrated on the synthesis techniques of SiNWs and recent progress on sensor development based on electrochemical methods, fluorescence field-effect transistors (FET), and surface-enhanced Raman scattering (SERS) spectroscopy. We also discussed the challenges of SiNW-based sensors in the future.